Solve :-
![(x - 1)(x - 2)(x - 3)(x - 4) = 8 (x - 1)(x - 2)(x - 3)(x - 4) = 8](https://tex.z-dn.net/?f=%28x+-+1%29%28x+-+2%29%28x+-+3%29%28x+-+4%29+%3D+8)
Answers
Answered by
7
Hey mate !!
Here's the answer !!
( x - 1 ) ( x - 2 ) ( x - 3 ) ( x - 4 ) = 8
=> ( x ² - 2x - x + 2 ) ( x² - 4x - 3x + 12 ) = 8
=> ( x² - 3x + 2 ) ( x² - 7x + 12 ) = 8
=> x⁴ - 7x³ + 12x² - 3x³ + 21x² - 36x + 2x² - 14x + 24 = 8
Combining the like terms, we get,
=> x⁴ - 10x³ + 35x² - 50x + 24 = 8
=> x⁴ - 10x³ + 35x² - 50x + 24 - 8 = 0
=> x⁴ - 10x³ + 35x² - 50x + 16 = 0
Solving the above equation, we get,
![x = \frac{- \sqrt{17} + 5}{2} , x = \frac{ \sqrt{17} +5}{2} x = \frac{- \sqrt{17} + 5}{2} , x = \frac{ \sqrt{17} +5}{2}](https://tex.z-dn.net/?f=x+%3D+%5Cfrac%7B-+%5Csqrt%7B17%7D+%2B+5%7D%7B2%7D+%2C+x+%3D+%5Cfrac%7B++%5Csqrt%7B17%7D+%2B5%7D%7B2%7D+)
Hope my answer helps !!
Cheers !!
Here's the answer !!
( x - 1 ) ( x - 2 ) ( x - 3 ) ( x - 4 ) = 8
=> ( x ² - 2x - x + 2 ) ( x² - 4x - 3x + 12 ) = 8
=> ( x² - 3x + 2 ) ( x² - 7x + 12 ) = 8
=> x⁴ - 7x³ + 12x² - 3x³ + 21x² - 36x + 2x² - 14x + 24 = 8
Combining the like terms, we get,
=> x⁴ - 10x³ + 35x² - 50x + 24 = 8
=> x⁴ - 10x³ + 35x² - 50x + 24 - 8 = 0
=> x⁴ - 10x³ + 35x² - 50x + 16 = 0
Solving the above equation, we get,
Hope my answer helps !!
Cheers !!
TANU81:
Idk the ans just trying to do.
Answered by
8
Hey friend, Harish here.
Here is your answer.
![\to (x^2 - 5 x + 2) (x^2 - 5 x + 8) = 0 \\ \\ \mathrm {Now, Let's \ Check \ the \ nature\ of\ roots \ of\ both\ quadratic\ equations} \\ \\ \mathrm{ In \ (x^2 - 5 x + 2) \ ; a = 1,b=-5,c=2 } \\ \\ Then,\ b^2 - 4ac = 25 - 28 = -3 \ \textless \ 0 \\ \\ \mathrm{Therefore\ it\ has\ no\ real\ roots} \\ \\ \mathrm{Then, The \ real\ value\ of\ x \ is \ the \ roots\ of\ (x^2 - 5 x + 2)}\\ \\ \mathrm{By\ Quadratic\ fromula} : \\ \\ \boxed{\bold{x=\frac{5-\sqrt{17}}{2},\:x=\frac{5+\sqrt{17}}{2}}} \to (x^2 - 5 x + 2) (x^2 - 5 x + 8) = 0 \\ \\ \mathrm {Now, Let's \ Check \ the \ nature\ of\ roots \ of\ both\ quadratic\ equations} \\ \\ \mathrm{ In \ (x^2 - 5 x + 2) \ ; a = 1,b=-5,c=2 } \\ \\ Then,\ b^2 - 4ac = 25 - 28 = -3 \ \textless \ 0 \\ \\ \mathrm{Therefore\ it\ has\ no\ real\ roots} \\ \\ \mathrm{Then, The \ real\ value\ of\ x \ is \ the \ roots\ of\ (x^2 - 5 x + 2)}\\ \\ \mathrm{By\ Quadratic\ fromula} : \\ \\ \boxed{\bold{x=\frac{5-\sqrt{17}}{2},\:x=\frac{5+\sqrt{17}}{2}}}](https://tex.z-dn.net/?f=+%5Cto+%28x%5E2+-+5+x+%2B+2%29+%28x%5E2+-+5+x+%2B+8%29+%3D+0+%5C%5C+%5C%5C+%5Cmathrm+%7BNow%2C+Let%27s+%5C+Check+%5C+the+%5C+nature%5C+of%5C+roots+%5C++of%5C+both%5C+quadratic%5C+equations%7D+%5C%5C+%5C%5C+%5Cmathrm%7B+In+%5C+%28x%5E2+-+5+x+%2B+2%29+%5C+%3B+a+%3D+1%2Cb%3D-5%2Cc%3D2+%7D+%5C%5C+%5C%5C+Then%2C%5C+b%5E2+-+4ac+%3D+25+-+28++%3D+-3+%5C+%5Ctextless+%5C++0++%5C%5C+%5C%5C+%5Cmathrm%7BTherefore%5C+it%5C+has%5C+no%5C+real%5C+roots%7D+%5C%5C+%5C%5C+%5Cmathrm%7BThen%2C+The+%5C+real%5C+value%5C+of%5C+x+%5C+is+%5C+the+%5C+roots%5C+of%5C+%28x%5E2+-+5+x+%2B+2%29%7D%5C%5C+%5C%5C+%5Cmathrm%7BBy%5C+Quadratic%5C+fromula%7D+%3A+%5C%5C+%5C%5C+%5Cboxed%7B%5Cbold%7Bx%3D%5Cfrac%7B5-%5Csqrt%7B17%7D%7D%7B2%7D%2C%5C%3Ax%3D%5Cfrac%7B5%2B%5Csqrt%7B17%7D%7D%7B2%7D%7D%7D+)
__________________________________________________
Hope my answer is helpful to you.
Here is your answer.
__________________________________________________
Hope my answer is helpful to you.
Similar questions